EFFECT OF DRYING METHODS ON QUALITY OF COTTON FIBERS BEFORE GINNING - Soomro, Noorullah (European Scientific Journal, ESJ, 2014)
The PCSI (Pakistan Cotton Standard Institute) standard test methods for measuring moisture percentage in Pakistan seed and lint cotton relate the drying system. The decline in weight is taken as the amount of moisture and is stated as a percentage (%) of the quantity of either the humid or dried material. It is essential to evaluate the standard methods and compare them to know that which drying method detoriates the cotton fibers to the minimum. Three cotton varieties MNH-93, Niab-78 and Ali Akbar-703 were taken to dry with natural, artificial drying methods and cotton storage technique. The fibers were tested for effective length, fineness and strength. It was observed that natural drying technique least influenced the cotton fiber properties whereas artificial drying technique the most. On the other hand storage technique detoriates at intermediate levels but does not reduce the moisture to the exact level required. Artificial drying technique proved to be fastest as the temperature control in this technique is in our hands.